2022
DOI: 10.1186/s12933-022-01616-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of soluble ST2, high-sensitivity cardiac troponin, and NT-proBNP in type 2 diabetes: a 15-year retrospective study

Abstract: Background Patients with type 2 diabetes (T2DM) present an increased risk of cardiovascular (CV) disease and excess CV-related mortality. Beyond the established role of brain natriuretic peptide (BNP) and cardiac troponins (cTn), other non-cardiac-specific biomarkers are emerging as predictors of CV outcomes in T2DM. Methods Serum levels of soluble suppression of tumorigenesis 2 (sST2), high-sensitivity (hs)-cTnI, and N-terminal (NT)-proBNP were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…NT-proBNP is strongly associated with adverse cardiovascular outcomes and mortality in HF populations [ 16 ] and plays an important role in the diagnosis and management of HF [ 17 , 18 ]. Beyond HF, NT-proBNP also has a good ability to predict death in general populations [ 10 ] and patients with DM [ 19 ]. Furthermore, a recent study from the Atherosclerosis Risk in Communities (ARIC) cohort showed that NT-proBNP discriminated mortality risk better than conventional risk factors only in subjects with DM instead of non-DM people after a median of 7.2 years of follow-up [ 11 ], which suggested that DM status may modify the relationship between NT-proBNP and risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is strongly associated with adverse cardiovascular outcomes and mortality in HF populations [ 16 ] and plays an important role in the diagnosis and management of HF [ 17 , 18 ]. Beyond HF, NT-proBNP also has a good ability to predict death in general populations [ 10 ] and patients with DM [ 19 ]. Furthermore, a recent study from the Atherosclerosis Risk in Communities (ARIC) cohort showed that NT-proBNP discriminated mortality risk better than conventional risk factors only in subjects with DM instead of non-DM people after a median of 7.2 years of follow-up [ 11 ], which suggested that DM status may modify the relationship between NT-proBNP and risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The ADVANCE study [30] and the EMPA-REG OUTCOME trial [31] showed that type 2 diabetic patients receiving glucose-lowering agents reduced their risk of MACE by 10-14%. Importantly, more of the recent studies demonstrated the prognostic value of sST2 in patients with diabetes: sST2, Hs-cTnI, and NT-proBNP are independently associated with mortality and onset of MACE in patients with diabetes; specifically, higher levels of sST2 led to an almost three-fold increase in the risk of death in a 15 year follow-up [32]. Additionally, sST2 remained a predictor of MACEs and mortality in patients with coronary artery disease, both with and without diabetes [33], as well as in patients with acute coronary syndrome and diabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] hs-troponin I is strongly associated with ischemic heart disease and other markers of end organ damage. 6,11,13 hs-troponin assays are the preferred biomarker by the American Heart Association for the detection of myocardial injury, 42 and both hs-troponin T and hs-troponin I are indicative of cardiomyocyte injury or necrosis. Prior studies have demonstrated that hs-troponin T and hs-troponin I are strongly associated with major adverse cardiovascular events, mortality, and rapid progression to symptomatic heart failure in asymptomatic adults.…”
Section: Table 3 Associations* (Or [95% Ci]) Of Clinical Categories O...mentioning
confidence: 99%
“…4,5 NT-proBNP (N-terminal pro-B-type natriuretic peptide), high-sensitivity cardiac troponin T (hs-troponin T), and high-sensitivity cardiac troponin I (hs-troponin I) are increasingly being recommended for risk stratification for a variety of cardiovascular outcomes. [6][7][8][9][10][11][12][13] NT-proBNP is used in the evaluation of heart failure and is a cleavage product of proBNP that is secreted by cardiomyocytes during ventricular stretch. 14 High-sensitivity assays for cardiac troponin T and I are biomarkers of myocardial damage.…”
mentioning
confidence: 99%